THE ROLE OF ALISHER NAVOI’S SUFIST VIEWS IN THE SPIRITUAL AND MORAL EDUCATION OF YOUTH IN THE CONDITIONS OF THE NEW UZBEKISTAN (Scientific journal of the Fergana State University, 2024)
The article analyzes the Sufi views of Alisher Navoi on the education of youth based on his works. Particular attention is paid to the basic requirements of the Naqshbandi teachings. The specific features of Sufism are revealed in connection with human spirituality. The requirements of a perfect person in Sufism have been studied. The role of Alisher Navoi’s views in the spiritual and moral education of youth in the conditions of the new Uzbekistan is also explored.